Gambaran Indeks Eritrosit Pada Pekerja Bengkel Motor Yang Terpapar Polusi Di Sekitar Jalan Vetran Selatan Kota Makassar - Nurhikma nurhikma; Suharsih Thahir; Rahima Rasyid (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
Workshop workers exposed to vehicle smoke pollution containing CO2, CO, and do not rule out the possibility of heavy metal Plumbum (Pb). They are people who in carrying out their work are exposed to high pollution. So that the body exposed to pollution will allow anemia. The erythrocyte index is a method of giving diagnostic and anemia classification. This study aims to determine the value of MCV, MCHC, and MCHC in workshop workers. The type of research is laboratory observation and sampling techniques are rangdom sampling. The samples in the study were 15 workers' venous blood workshops. The results of this study were presented in descriptive form using table statistics. The results obtained from 15 workshop workers by performing an erythrocyte index examination showed a low MCV value (7%), normal MCV (73%), increased MCV (20%), low MCH (7%), normal MCH (86%), MCH increases (7%), MCHC is low (0%), MCHC is normal (100%), MCHC increases (0%). It is recommended that workshop workers consume nutritious foods and wear personal protective equipment.